JUSTIFICATION OF THE PARAMETERS CHOICE FOR DETERMINING VISIBILITY OF ROAD OBJECTS IN THE DARK FOR THE EXAMINATION OF ACCIDENT - Шаша, Ігор Костянтинович; Сазонов, Олег Григорович; Гаркавцев, Євгеній Ігорович; Чудовський, Вадим Ігорович (Eastern-European Journal of Enterprise Technologies, 2010)
This article is devoted to the urgent problem of improving conduction of traffic accident’s motor and technical examination with the help of determining visible range of traffic objects at night time under the conditions of having inaccurate and indeterminate initial data.